Tissue Distribution and Nutritional Regulation of Fatty Acid-Binding Proteins (fabps) in Two Marine Teleosts, Turbot (Scophthalmus maximus), and Tiger Puffer (Takifugu rubripes). (24th March 2022) - Wang, Dixin; Zhao, Lili; Liao, Zhangbin; Bi, Qingzhu; Meng, Xiaoxue; Duan, Mei; Ma, Qiang; Wei, Yuliang; Cao, Lin; Liang, Mengqing; Xu, Houguo
Abstract : Fatty acid-binding proteins (fabps) play important roles in lipid homeostasis. In the present study, 7 fabp isoforms, namely, fabp1, fabp2, fabp3, fabp4, fabp6, fabp7, and fabp10, in two marine teleosts, were characterized. In general, turbot and tiger puffer fabp genes showed high identity to their orthologs in other fish species and mammals, but tiger puffer Fabp6 shared the lowest identity to its known orthologs in zebrafish and human. The tissue distribution patterns of fabps were generally in accordance with their function features. However, tiger puffer fabps, in particular Fabp1, Fabp2, Fabp6 and Fabp7, may have functions distinct from other teleosts, as indicated by the phylogenetic tree and tissue distribution patterns. In both species, high dietary lipid levels downregulated the expression of fabp2, fabp3, fabp6, and fabp7a but tended to upregulate the fabp1 expression. Starvation downregulated the expression of most fabps in both fish species, but the downregulation of fabp expression in turbot was much more drastic and earlier compared to tiger puffer. Long-term (30-day) starvation increased the fabp7 expression in tiger puffer and tended to increase the fabp6 expression in turbot. Results of this study contribute to fish fabp physiology and its nutritional regulation.